The metabolic fate of [14C]-fenclozic acid in the hepatic reductase null (HRN) mouse. (10th December 2013) - Pickup, Kathryn; Wills, Jonathan; Rodrigues, Alison; Jones, Huw B.; Page, Chris; Martin, Scott; Sarda, Sunil; Wilson, Ian
Abstract: 1. The distribution, metabolism, excretion and hepatic effects of fenclozic acid were investigated following a single oral dose of 10 mg/kg to hepatic reductase null (HRN) mice. 2. The majority of the [ 14 C]-fenclozic acid was eliminated via the urine/aqueous cage wash, (55 %) with a smaller portion excreted in the faeces, (5 %). The total recovery of radioactivity in the excreta over the 72 h period studied was ca . 60%. 3. Metabolism of fenclozic acid in the HRN mice was entirely to the carboxylic acid function and was dominated by amino acid conjugation to glycine and taurine, with lesser amounts of an acyl glucuronide. 4. Whole body autoradiography of mice showed general distribution into all tissues except the brain. Radioactivity was still detectable in the kidney and liver of the HRN mice at 72 h post-dose. Covalent binding studies showed evidence of binding to kidney, liver and plasma proteins however, the degree of binding was less than 50 pmol equiv/mg protein for all tissues. 5. The HRN mouse appears to be a useful in vivo model for the study of the Phase II conjugation metabolism of fenclozic acid in the absence of hepatic cytochrome P450-related oxidative metabolism.